2013
DOI: 10.1177/0898264313484058
|View full text |Cite
|
Sign up to set email alerts
|

Pain and Use of Alcohol in Later Life

Abstract: Objective To determine whether (a) late-life pain predicts growth in older adults’ use of alcohol, and elevated risk of drinking problems; and (b) sociodemographic characteristics moderate these relationships. Method Five times over an 8-year interval, N = 5,446 Health and Retirement Study (HRS) participants provided information about their pain and alcohol use. Two-part latent growth modeling and logistic regression were used to analyze these data. Results Participants with more pain at baseline had lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 51 publications
1
16
1
Order By: Relevance
“…In the same sample, results further indicated that greater pain unpleasantness was associated with more severe alcohol dependence, independent of relevant sociodemographic and mental health factors (Lawton & Simpson, 2009). Similar findings revealed that older adults who endorsed more severe pain and greater pain-related interference with daily activities (compared to those with no pain) were 20% and 50% more likely to also have endorsed current drinking problems, respectively (Brennan & Soohoo, 2013). Among older adults, a greater number of painful medical conditions has been associated with increased frequency of experiencing drinking problems (Brennan et al, 2011).…”
Section: Effects Of Pain On Alcohol Usementioning
confidence: 64%
See 4 more Smart Citations
“…In the same sample, results further indicated that greater pain unpleasantness was associated with more severe alcohol dependence, independent of relevant sociodemographic and mental health factors (Lawton & Simpson, 2009). Similar findings revealed that older adults who endorsed more severe pain and greater pain-related interference with daily activities (compared to those with no pain) were 20% and 50% more likely to also have endorsed current drinking problems, respectively (Brennan & Soohoo, 2013). Among older adults, a greater number of painful medical conditions has been associated with increased frequency of experiencing drinking problems (Brennan et al, 2011).…”
Section: Effects Of Pain On Alcohol Usementioning
confidence: 64%
“…There is also evidence that men are more likely to drink alcohol to cope with stress (Esper & Furtado, 2013), and men have also been shown to endorse drinking to cope with pain (Brennan et al, 2005; Riley, Gilbert, & Heft, 2002). Although aging has generally been associated with decreased alcohol consumption (e.g., Shaw, Krause, Liang, & McGeever, 2011), there is some evidence to suggest that older adults who experience painful medical conditions may experience drinking problems more often than older adults without painful medical conditions (Brennan, Schutte, SooHoo, & Moos, 2011; Brennan & Soohoo, 2013), and the likelihood of experiencing chronic pain has been shown to increase with age (Tsang et al, 2008). With regard to race and ethnicity, relative to Caucasians, African-Americans who seek treatment for chronic pain tend to endorse more persistent pain and greater unpleasantness (e.g., Edwards, Fillingim, & Keefe, 2001).…”
Section: Estimates Of Co-occurring Pain and Alcohol Usementioning
confidence: 99%
See 3 more Smart Citations